2015
DOI: 10.1007/s11626-015-9958-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosiglitazone on proliferation and differentiation of duck preadipocytes

Abstract: Rosiglitazone (RSG), one member of the thiazolidinediones (TZDs), is a type of anti-diabetic drug in diabetic humans and animal models, whose function remains unknown in waterfowl. In this study, effects of RSG on duck preadipocyte differentiation were investigated. We detected cell viability using CCK method and measured the mRNA expression of key genes and protein contents involved in preadipocyte differentiation via qRT-PCR and ELISA kits, respectively. Lipid accumulation was determined via Oil Red O staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Staining of intracellular lipids by Oil Red O was performed as described previously 11 . To quantify intracellular triglyceride accumulation, cells were washed with PBS twice.…”
Section: Methodsmentioning
confidence: 99%
“…Staining of intracellular lipids by Oil Red O was performed as described previously 11 . To quantify intracellular triglyceride accumulation, cells were washed with PBS twice.…”
Section: Methodsmentioning
confidence: 99%
“…8,11 ROZ, a peroxisome proliferator-activated receptor-γ (PPAR-γ) agonist, is mainly used clinically for the treatment of type 2 diabetes. 12 Studies have found that it can induce adipogenesis and then promote the proliferation of fat cells, inhibit the possibility of cancer cell metastasis, and treat tumors. 13 In the combination of DAS and ROZ, DAS inhibits the mitogen-activated protein kinase pathway, interferes with the proliferation and differentiation of tumor cells, keeps tumor cells in the late stage of mitosis.…”
Section: Introductionmentioning
confidence: 99%